Makna Generasi Sandwich Pada Film Cinta Pertama, Kedua, dan Ketiga (Analisis Semiotika Charles Sanders Peirce) - Putri, Paramitha Amelia; Prasetio, Arie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Indonesia is facing the phenomenon of the sandwich generation, which plays a dual role in the financial affairs of three generations at once. Data from the March 2022 National Socio-Economic Survey shows that 8.4 million Indonesians (62.71%) belong to the sandwich generation. The movie